Exploring The Effect of [HuArgI (Co)-PEG5000]-Induced Autophagy on The Migration, Adhesion, And Invasion of U87 Glioblastoma cells - Haidar, Sara (2024)
Thesis (M.S.) -- Biological Sciences, May 2024.